IκB Kinase Inhibitor VII Modulates Sepsis-Induced Excessive Inflammation and Cardiac Dysfunction in 5/6 Nephrectomized Mice - Mei Ding; Dede Lian; Lirong Zhang; Tiechao Jiang; Wei Wang (Mediators of Inflammation)
Background. Chronic kidney disease condition requires regular dialysis; the patients have greater risk of sepsis and have high mortality rate compared to general people with sepsis. The adverse cardiac condition leads to mortality in subjects with sepsis. In the present work, we studied the consequences of chronic kidney damage by 5/6 nephrectomy on cardiac function in mice induced with sepsis and the mechanism involved. Methods. We used C57BL/6 mice and subjected them to 5/6 nephrectomy; after induction of chronic kidney damage, they were subjected to sepsis by either LPS treatment or by cecal ligation and puncture (CLP) method. The cardiac function test was done by echocardiography. Protein expression was done by western blot analysis. Results. The 5/6 nephrectomized mice showed significant increase in blood creatinine and urea levels compared to sham-operated mice; the mice also showed decreased ejection fraction and increased levels of phosphorylated IkBα and nuclear translocation of the NF-κB and inducible nitric oxide synthase (iNOS). When subjected to CLP and LPS treatment, the 5/6 nephrectomized mice augmented cardiac abnormalities and lung inflammation and increased plasma levels of TNF-α, IL-1, IL-12, and IL-18. Also, we evidenced increased levels of p-IKKα/β and Ikβα, NF-κβ, and iNOS. Treatment of IKK inhibitor VII in 5/6 nephrectomized mice after LPS administration or CLP attenuated these effects. Conclusion. Chronic kidney disease could lead to abnormal cardiac function caused by sepsis in mice; this may be due to increased expression of NF-κβ and iNOS in cardiac tissues.